Orthophoto Classification for UGV Path Planning using Heterogeneous Computing. (11th June 2013) - Hudjakov, Robert; Tamre, Mart
We have developed a system that uses aerial imagery for improving unmanned ground vehicle navigation capabilities. The current article focuses on the viability of using heterogeneous computing architecture for improving system performance in terms of energy consumption and area analysed per second.